Analysis of Website Based Information System Development Methods - Sarah Zeva (AGUSPATI RESEARCH INSTITUTA, 2023)
Currently the development of information technology is very fast. Information technology is needed in human life. One of the functions of information system technology is to help or encourage human work to run more effectively and efficiently. Information system development has many methods and various platforms. Platforms that can be used in the development of information systems are mobile, web, or desktop-based platforms. This study aims to determine a website-based information system development model, and the data is obtained through relevant literature from 2016 to 2020. The method used in this study is the System Literature Review (SLR). The SLR method is used to identify, review, evaluate and interpret all available research in the subject area of the phenomenon of interest, as well as specific related research questions. Using the SLR method, journal articles can be systematically reviewed and identified, and predetermined steps or procedures can be followed in each process. The results of this study indicate the main method used in the development of website-based information systems and the advantages and disadvantages of developing website-based information systems used in this study.